Perceptions of Health, Body Size, and Nutritional Risk Factors for Obesity in People with HIV in South Africa. - Manne-Goehler, Jennifer; Rahim, Nicholas; van Empel, Eva; de Vlieg, Rebecca; Chamberlin, Grace; Ihama, Amanda; Castle, Alison; Mabweazara, Smart; Venter, Willem D. F.; Chandiwana, Nomathemba; Levitt, Naomi S.; Siedner, Mark (AIDS & Behavior, 2024)
Metabolic disease is increasing in people with HIV (PWH) in South Africa, but little is known about self-perceptions of body size, health, and nutritional behavior in this population. We performed a cross-sectional analysis of individual-level data from the 2016 South Africa Demographic and Health Survey. This survey measured HIV serostatus and body mass index (BMI). We categorized participants into six BMI groups: 18.5–22 kg/m2, 22–25 kg/m2, 25–27.5 kg/m2, 27.5–30 kg/m2, 30–35 kg/m2, and ≥ 35 kg/m2 and stratified them by HIV serostatus. Our outcomes were self-reported (1) body size and (2) health status among all participants, and intake of (3) chips and (4) sugar-sweetened beverages (SSB) in PWH. We described these metrics and used multivariable regression to evaluate the relationship between the nutritional behaviors and BMI ≥ 25 kg/m2 in PWH only, adjusting for age, sex, educational attainment, and household wealth quintile. Of 6138 participants, 1163 (19.7%) were PWH. Among PWH, < 10% with a BMI 25–30 kg/m2, < 20% with a BMI 30–35 kg/m2 and < 50% with a BMI ≥ 35 kg/m2 self-reported as overweight or obese. PWH reported being in poor health at higher rates than those without HIV at each BMI category except ≥ 35 kg/m2. In adjusted models, SSB consumption was associated with BMI ≥ 25 kg/m2 (1.13 [1.01–1.25], t-statistic = 2.14, p = 0.033) in PWH. Perceptions of body size may challenge efforts to prevent weight gain in PWH in South Africa. SSB intake reduction should be further explored as a modifiable risk factor for obesity.